Conceptualizing Environmental Citizenship for 21st Century Education - Hadjichambis, Andreas Ch; Reis, Pedro; Paraskeva-Hadjichambi, Demetra; Činčera, Jan; Boeve-de Pauw, Jelle; Gericke, Niklas; Knippels, Marie-Christine (Environmental Discourses in Science Education,, 2020)
XIII, 261 p. 26 illus.